Men are from Mars, women are from Venus : a practical guide for improving communication and getting what you want in your relationships - Gray, John, 1951- (New York, NY : HarperCollins, 1992)
Popular marriage counselor and seminar leader John Gray provides a unique, practical and proven way for men and women to communicate and relate better by acknowledging the differences between them. Once upon a time Martians and Venusians met, fell in love, and had happy relationships together because they respected and accepted their differences. Then they came to earth and amnesia set in: they forgot they were from different planets. Using this metaphor to illustrate the commonly occurring conflicts between men and women, Gray explains how these differences can come between the sexes and prohibit mutually fulfilling loving relationships. Based on years of successful counseling of couples, he gives advice on how to counteract these differences in communication styles, emotional needs and modes of behavior to promote a greater understanding between individual partners. Gray shows how men and women react differently in conversation and how their relationships are affected by male intimacy cycles ("get close", "back off"), and female self-esteem fluctuations ("I'm okay", "I'm not okay"). He encourages readers to accept the other gender's particular way of expressing love, and helps men and women learn how to fulfill each other's emotional needs. With practical suggestions on how to reduce conflict, crucial information on how to interpret a partner's behavior and methods for preventing emotional "trash from the past" from invading new relationships, Men Are from Mars, Women Are from Venus is a valuable tool for couples who want to develop deeper and more satisfying relationships with their partners.
Men are from Mars, women are from Venus -- Mr. Fix-It and the home-improvement committee -- Men go to their caves and women talk -- How to motivate the opposite sex -- Speaking different languages -- Men are like rubber bands -- Women are like waves -- Discovering our different emotional needs -- How to avoid arguments -- Scoring points with the opposite sex -- How to communicate difficult feelings -- How to ask for support and get it -- Keeping the magic of love alive.
Keywords: Marriage; Communication in marriage; Interpersonal relations